IMPLEMENTASI ETIKA BISNIS ISLAM DALAM PENGELOLAAN HCG (HIKMA COLLECTION GROUP) DI PONDOK PESANTREN MIFTAHUL HIKMAH KARANG KECAMATAN PARENGAN KABUPATAN TUBAN - Mela Anggilia; Joko Hadi Purnomo; Niswatin Nurul Hidayati (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2021)
The purpose of this study is to describe and analyze the implementation of Islamic business ethics in the management of HCG (Hikma Collection Group) at Miftahul Hikmah Parengan Tuban, as well as the obstacles faced. This study used qualitative research methods. The results of this study are the implementation of Islamic business ethics in the management of HCG (Hikma Collection Group) using eight principles that are in accordance with Islamic teachings, namely the first with the principle of honesty in business, the second with the principle of selling good quality goods. The third principle is not selling out promises to consumers who want to buy at HCG (Hikma Collection Group). The fourth principle applied in HCG (Hikma Collection Group) is to be responsible in doing business regarding dissatisfaction in front of consumers and being responsible before God. The fifth principle is non-binding and generous to customers and all employees by getting used to being polite, smiling, greeting and friendly to all consumers and each employee. The sixth principle is the balance of doing business by always prioritizing the unity of every employee in HCG (Hikma Collection Group). The seventh principle is discipline in administration that uses honesty and timeliness in completing administrative reports. The last principle is to complete the product according to the target desired by the consumer. In addition, there are also several supporting and inhibiting factors in the implementation of Islamic business ethics in the institution.